Factors Affecting The Perceived Hospital Quality, - Toker, F., Korkmaz, M., Yücel, A. S.,Kılıç, B., (My University, 2014)
Quality perception, which is related to a number of factors and variables, has come to the fore both because of the features of health services and because of the hospital quality rating practices of the Ministry of Health in Turkey. Although there are national and international studies to assess the perceived quality, with the thought that countryspecific studies are not enough, this study has been thought necessary in order to learn the main factors which affect public's hospital quality perception in Turkey due to the facts that culture is an important determinant on quality perception and the results of the year-to-date studies are different from each other. In Turkey's 3 biggest cities, 2500 people have been asked 28 questions with demographical and descriptive features in the questionaire in order to define hospital quality and these questions have been perceived in 4 dimensions. Non-parametric and parametric statistical tests have been applied on the data gathered. In the scope of analysis, descriptive statistics, reliability analysis, ANOVA analysis, and Regression analyses have been used. According to the results of this study, the idea of a high quality hospital changes according to age, income, education and the city; the tendency to the idea of a well managed hospital changes according to gender, income, education, and the city and the idea of low-quality changes according to age, gender, income, education and the city. Whereas education is the most effective variable in high-quality hospital aspect, gender is the most effective variable on low-quality hospital. In this study, it has been determined that hospital quality perception changes according to the demographical features as age, income, education and the city resided. This study has been reinforced with the fact that there has been a significant difference in terms of age groups and level of education in Devebakan and Aksaraylı's study in a private hospital with SERVQUAL scale. We are made to think that these researches has to be carried out more owing to the fact that there has been similar and different results with different scales in different organizations.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Quality; Hospital; Health; Health services